Central Venous Catheter Impacted into the Tricuspid Annulus over a Quarter Century - Laszlo Gobolos; Szabolcs Miskolczi; Laszlo Hejjel; Attila Konyi (Journal of Surgery and Surgical Research - Peertechz Publications, 2015)
A 58-year-old woman was referred for elective coronary bypass graft surgery (CABG). As an incidental finding, the coronary angiogram showed a radio-opaque linear foreign body in the superior vena caval-right atrial region; additionally to a significant flow limiting multivessel coronary artery disease (Panels A, B). The nature of the foreign body was initially unclear; the patient did not give a history of penetrating chest trauma or other major diseases. Further anamnestic review revealed a suicidal attempt 25 years before, which lead to a short intensive care stay. The patient underwent a conventional triple vessel CABG. After opening the right atrium, a fractured old-fashioned central venous cannula (CVC) was found being impacted with the tip into the tricuspid annulus; the curvature accurately shaped the route through superior vena cava to the tricuspid valve (Panels C, D). Following removal of the foreign body the patient had an uneventful postoperative course.